Upaya Peningkatan Literasi Keuangan UMKM Nasabah BTPN Syariah Kecamatan Pucuk - Rangga Eka Saputra; Yanda Bara Kusuma (Institut Teknologi dan Bisnis Semarang, 2024)
UMKM (Micro, Small, and Medium Enterprises) face various challenges, and one of the most common is making inaccurate decisions. These inaccurate decisions are often due to the lack of available information at the time of decision-making. In business, decisions can involve both financial and non-financial aspects. Financial decisions heavily rely on accounting information. Unfortunately, the accounting information generated by UMKM still faces many problems. One of the biggest issues is that the majority of UMKM have not yet prepared financial statements. Therefore, this activity is held in the form of a simple financial recording training targeted at UMKM. The implementation of this activity includes three stages: first, the assessment stage; second, the delivery of material and practice; and third, the evaluation and reporting stage.